Metaxia Tsipopoulou. Petras, Siteia I. A Minoan Palatial Settlement in Eastern Crete. Excavation of Houses I.1 and I.2. - Schoep, Ilse (Journal of Greek Archaeology, 2019)
This volume is the third in a series that publishes the final results of the excavations at Petras. The first volume was dedicated to the Cretan Hieroglyphic archive from the palace, the second to the proceedings of the first Petras symposium that took place in 2010. Since the publication of the volume under review in 2016, the second Petras symposium that took place in 2015 has also been published.